Community Empowerment Through the Pesona Sumpur Tourism Awareness Group in the Kampuang Minang Tourism Village Nagari Sumpur - Putri, Aisya Indriani; Solfema, Solfema (Universitas Negeri Padang, 2025)
Community empowerment is one of the efforts that can be done by providing resources, opportunities, knowledge, and skills to the community to improve their ability to become independent and prosperous. In an effort to empower the community, it can be done by holding programs that aim to empower the community. Therefore, this research aims to analyze the stages, facilities, community participation, and program impacts of the community empowerment program carried out by the Pesona Sumpur Tourism Awareness Group in Kampuang Minang Tourism Village Nagari Sumpur West Sumatra. So that it can be known regarding what empowerment programs are implemented. The type of research used is qualitative research with a case study method, data obtained through observation, interviews, and document review. The subjects in this study were 4 people and the research informants totaled 4 people.The results show that the stages of the community empowerment program include identification of needs, planning, development, implementation, and evaluation. The programs implemented include river tubing training, article writing training, traditional speech training. This program has a positive impact in the form of increased income, cultural preservation, and additional knowledge and skills. Community participation is carried out using the CBT or Community Based Tourism approach which aims to enable the community to participate in all forms of activities carried out. In addition to community participation, support from various parties is the key to success so that every activity carried out in various community empowerment programs can be carried out properly.